2020
DOI: 10.1007/s00228-020-02941-w
|View full text |Cite
|
Sign up to set email alerts
|

What about COVID-19 and arachidonic acid pathway?

Abstract: Background and objective COVID-19 is a highly contagious viral disease. In this study, we tried to define and discuss all the findings on the potential association between arachidonic acid (AA) pathway and COVID-19 pathophysiology. Methods A literature search across PubMed, Scopus, Embase, and Cochrane database was conducted. A total of 25 studies were identified. Results The data elucidated that COX-2 and prostaglandins (PGs), particularly PGE 2 , have pro-inflammatory action in COVID-19 pathophysiology. Arac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 28 publications
2
70
0
Order By: Relevance
“…Cyclooxygenase-2 (COX-2) is a rate-limiting enzyme for the generation of PGE2 and Hydroxyprostaglandin Dehydrogenase 15-(NAD) (HPGD) is an enzyme responsible for the degradation of PGE2 29 . These ndings, supported further by a recent literature review 30 naturally suggested a connection between arachidonic acid metabolism and PGE2 in COVID-19 disease.…”
Section: Introductionsupporting
confidence: 69%
“…Cyclooxygenase-2 (COX-2) is a rate-limiting enzyme for the generation of PGE2 and Hydroxyprostaglandin Dehydrogenase 15-(NAD) (HPGD) is an enzyme responsible for the degradation of PGE2 29 . These ndings, supported further by a recent literature review 30 naturally suggested a connection between arachidonic acid metabolism and PGE2 in COVID-19 disease.…”
Section: Introductionsupporting
confidence: 69%
“…Beyond the proinflammatory cytokines, also the products of lipid metabolism, namely arachidonic acid (AA) derivates—prostaglandins, leukotrienes, and thromboxane—act as proinflammatory mediators in COVID-19 and AA-deficient patients are more susceptible to a severe course of SARS-CoV-2 infection [ 59 ]. However, more studies are needed to elucidate the involvement of these pathways since inhibiting AA mediators brought conflicting results and other studies have questioned the role of AA inhibitors, such as nonsteroidal anti-inflammatory drugs (NSAID) and ibuprofen, in the worsening of COVID-19 [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hijacking of the cellular amino acid metabolism to fuel viral proliferation might be a critical mechanism underlying the COVID-19 pathogenesis [ 34 ]. Arachidonic acid is an endogenous bioactive antiviral lipid, and this metabolic pathway has been suggested to play an important role in susceptibility to COVID-19 [ 35 , 36 ]. The elevated levels of free poly-unsaturated fatty acids are characteristics of COVID-19 patients [ 10 , 37 ].…”
Section: Discussionmentioning
confidence: 99%